2020
DOI: 10.1021/acs.est.0c01110
|View full text |Cite
|
Sign up to set email alerts
|

Excitation–Emission Matrix Spectroscopy for Analysis of Chemical Composition of Combustion Generated Particulate Matter

Abstract: Analysis of particulate matter (PM) is critical for the assessment of human exposures to potentially harmful agents, notably combustion-generated PM; specifically polycyclic aromatic hydrocarbons (PAHs) found in them and associated with carcinogenic and mutagenic effects. In this study, we quantify the presence and concentrations of PAHs with low molecular weight (LMW) and higher molecular weight (HMW) in combustion-generated PM using excitation-emission matrix (EEM) fluorescence spectroscopy. PM samples were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 103 publications
1
15
0
Order By: Relevance
“…Mahamuni et al reported the wood smoke samples' chemical composition, calculating that the total mass of 16 EPA PAHs was~20-25 ng/μg of soot, see S6 Fig in S1 File. About 75% (by weight) of PAHs in the sample were high species with MW>202 g/mol (i.e., larger than Pyrene) [13]. TOC analysis was not performed here but typically reported TOC values for cookstoves are greater than 50% depending on the type of the cookstove and operational conditions [38][39][40].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Mahamuni et al reported the wood smoke samples' chemical composition, calculating that the total mass of 16 EPA PAHs was~20-25 ng/μg of soot, see S6 Fig in S1 File. About 75% (by weight) of PAHs in the sample were high species with MW>202 g/mol (i.e., larger than Pyrene) [13]. TOC analysis was not performed here but typically reported TOC values for cookstoves are greater than 50% depending on the type of the cookstove and operational conditions [38][39][40].…”
Section: Plos Onementioning
confidence: 99%
“…EEM has been previously used for analysis of combustion PM [28][29][30][31]. The challenges of deconvolving the overlapping peaks can be addressed by data-driven techniques [13,32]. However, similar to the standard laboratory methods, EEM analysis of aerosol samples suffers labor-intensive steps involving sample collection on filters, solvent extraction, filtration, and serial dilutions, which is not amenable for miniaturized sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, prior works focused on the variability of the overall BrC mass fractions and their overall light-absorption properties measured at various settings in laboratory flame experiments, such as flame temperature, dilution, equivalence ratio, and height above the burner distance. , Chemical species in flame emissions may span hundreds to thousands of organic compounds that usually make up a smaller mass fraction of OC compared to that of the BC generated in flames . Of the OC species formed in the flame combustion of ethylene, , benzene, , toluene, and an A-1 jet fuel surrogate, , large-molecular-weight PAHs and their oxidized byproducts were reported, as well as hydrocarbons with more aliphatic-like structures and higher oxygen content. Additional microscopic imaging of individual particles from these studies , showed their liquid-like appearance and morphological properties, indicating a graphitic core and a more aliphatic shell.…”
Section: Introductionmentioning
confidence: 99%
“…22 These system characteristics have been leveraged for material synthesis and studies of particle formation and growth in dilute low temperature flames. [23][24][25] While some hydrothermal flame reactors are operated in the upright configuration, 26 these provide high flame temperatures but very low residence time. Most SCWO reactors utilize the downflow arrangement 5,12,[27][28][29] to achieve long residence times and uniform temperature profiles needed for hazardous waste destruction.…”
Section: Introductionmentioning
confidence: 99%